Management Of Suryavarta With Katphala Churna Nasya And Danti Pravala Yoga W.S.R. To Frontal Sinusitis - Bhardwaj, Vijayant; Sharma, Satish; Bala, Anju; Thakur, Priyanka (International Research Journal of Ayurveda & Yoga, 2020)
Suryavarta is one of Shiroroga described by Acharyas characterised by headache which start early in morning and increases as day passes and become maximum at noon and is a Tridoshaja vyadhi. As its symptoms ressemble frontal headache this was selected for study . The present study was done on 29 patients of Suryavarta , who were grouped into three groups with 9 patients in first group, 9 patients in second group and 11 patients in third group. Group I was treated with Katphala churna nasya, Group II was treated with Danti pravala yoga as oral drug and in Group III both therapies was given. The signs and symptoms were studied before and after the treatment. Results of study show better results in Group III as 50% patients were markedly improved, 40% were mildly improved and 10% were cured.